Answer:
G) the expression has the greatest value when 6.
ie, [tex]xy=b[/tex]
Step-by-step explanation:
F) Given expression is -xy and to find the greatest value of that expression when [tex]x=-2[/tex] and [tex]y=-3[/tex]
Substitute the given values of [tex]x=-2[/tex] and [tex]y=-3[/tex] is the given expression
[tex]-xy=-(2)(-3)[/tex]
[tex]=-(6)[/tex]
[tex]-xy=-6\hfill(1)[/tex]
h) x-y
Given expression is x-y
substitute x=-2, y=-3 is above expression we get
[tex]x-y=-2-(3)[/tex]
[tex]-2+3[/tex]
[tex]x-y=1\hfill(2)[/tex]
G, xy
Given expression is xy
Substitute x=-2, y=-3 in above expression
[tex]xy=(-2)(-3)[/tex]
[tex]xy=6\hfill(3)[/tex]
I) -x-y
Given expression is -x-y
put x=-2, y=-3 in above expression
[tex]-x-y=-(-2)-(-3)[/tex]
[tex]=2+3[/tex]
[tex]-x-y=5\hfill(4)[/tex]
Now comparing the greatest values equation (1), (2), (3) and (4) we get
Equation (3) xy=6 has the greatest value